The complete chloroplast genomes and comparative study of the two tung trees of Vernicia (Euphorbiaceae) - Zhenzhou Chu; Yuwei Wang; Jianjun Yang; Gulbar Yisilam; Jialei Li; Xinmin Tian (BMC Genomics)
Abstract Background Vernicia montana and V. fordii are economically important woody oil species in the Euphorbiaceae that have great industrial oil and ornamental greening properties, however, the wild resources of Vernicia trees have been reduced because of their habitat destruction. Considering the diverse economic and ecological importance of Vernicia species, it is important to collect more molecular data to determine the genetic differences between V. montana and V. fordii. Results We sequenced, assembled, and annotated the complete chloroplast (CP) genome of two tung trees based on the genome skimming approach. The whole CP genomes of V. montana and V. fordii were 163,518 bp and 161,495 bp in length, both including a pair of inverted repeats separated by a large single-copy and a small single-copy region. We detected a total number of 311 tandem repeats, 100 dispersed repeats, and 255 simple repeats from V. montana and V. fordii CP genomes. The mean value of nucleotide diversity between the two species was 0.0122, and the average Ka/Ks ratio across all coding genes was 0.3483. Comparative chloroplast genome analysis showed that the coding regions were more conserved than the non-coding regions. The phylogenetic relationships yielded by the complete genome sequences showed that V. montana was closely related to V. fordii and is considered as a sister group. Conclusions We sequenced, assembled, annotated, and analyzed the CP genome of two tung trees, which will be useful in investigating the conservation genetics and potential breeding applications of this oil shrub.